Development and characterization of propolis wax-based oleogel emulsion and its application as shortening replacer in cake - Nasirzadeh, Roghayeh; Roufegarinejad, Leila; Tabibiazar, Mahnaz; Alizadeh, Ainaz; Khiabani, Arezou Habibzadeh (SPRINGER, 2024)
This study aimed to develop an oleogel emulsion based on propolis wax (PW) as a potential shortening replacement and reducing the fat content in the cake. According to the microstructure study, the increase in PW concentration increased the number of needle-like crystals, and the increase in oleogel content in the emulsion decreased the size of water droplets. The increasing PW oleogel content in the emulsions enhanced the gel strength, and the emulsions showed a shear-thinning behavior. The smallest particle size was related to the emulsions with 4%wt of PW (60-120 nm). The oxidative stability and oil binding capacity in emulsions were significantly (P < 0.05) improved by increasing oleogel content and the concentration of PW. The emulsion with 4%wt of PW and 50% water content (PW4-E50) was selected as an optimized sample for application in the cake as a shortening replacer. Among the samples, PW4-E50 was chosen as optimized samples in cake formulation due to its lower peroxide value at the end of the 30 day (10.32 +/- 0.32 meq O2/kg), highest oil binding capacity (82.52 +/- 0.53%), and zeta potential (+ 56.96 +/- 0.35 mv). As a result, textural properties revealed that cakes fabricated with emulsions at three substitution levels exhibited a satisfactory texture profile compared to cakes based on oleogel. Formulated cakes with oleogel and emulsion obtained the lowest L* and b* values. The Oleogel emulsion replacing 40% of cake shortening (PW-E40) demonstrated the highest overall acceptability.
Keywords: Emulsion; Propolis wax; Saturated fat; Oil structuring; Solid fats; Bakery products; OIL; BEESWAX; GEL; Food Science & Technology